СТАНОВИЩЕ ЄВРЕЙСЬКОГО НАСЕЛЕННЯ В УКРАЇНСЬКІЙ НАРОДНІЙ РЕСПУБЛІЦІ (Zaporizhzhia Historical Review, 2021)
This scientific article is devoted to the position of Jewish parties in the history of Ukraine. Their attitudes and also he relation of Ukrainian power are reflected toward them.